The Effect of Top-Down and Bottom-Up Strategies on Students' Listening Skill - Manihuruk, Leonita Maria Efipanias; Sidabutar, Yanti Arasi (Jurnal Basicedu, 2022)
The purpose of this study was to determine whether the Top Down and Bottom Up strategies had a significant effect on students' listening skills. This research was conducted with quantitative experimental research. The population of this research is the third semester students of HKBP Nommensen, Pematangsiantar University. The samples of this study were two classes which were selected by random sampling. There are 60 students. Class I as many as 30 students as the experimental group who were taught using the Top Down and Bottom Up Strategy and class II as many as 30 students as the control group who were taught without using the Top Down and Bottom Up Strategy. The instrument for collecting data is a test. To obtain the reliability of the test used the Kuder Richardson formula (KR21). The results showed that there was a significant effect of using Top Down and Bottom Up Strategies on students' listening skills.